Meningkatkan Hasil Belajar Siswa pada Materi Benda Zat Tunggal dan Campuran Melalui Model Snowball Throwing dan Media Kartu Pintar Kelas V SDN Talaga Jaya - Rahmatia Suleman; Irvin Novita Arifin; Gamar Abdullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Rahmatia Suleman, 2024. Improving the Learning Outcomes of Pure Substance and Mixtures Material using Snowball Throwing Model and Smart Card Media for Students in Class V of SDN 3 Talaga Jaya. Undergraduate Thesis. Department of Elementary Teacher Education, Faculty of Education, Universitas Negeri Gorontalo. The principal supervisor is Dr. Irvin Novita Arifin, S.Pd., M.Pd., and the co-supervisor is Dr. Gamar Abdullah, S.Si., M.Pd.The problem statement of this research is